T cell receptor signaling for γδT cell development - Muro, Ryunosuke (Inflamm Regen, 2019)
T cells are central to the vertebrate immune system. Two distinct types of T cells, αβT and γδT cells, express different types of T cell antigen receptors (TCRs), αβTCR and γδTCR, respectively, that are composed of different sets of somatically rearranged TCR chains and CD3 subunits. γδT cells have recently attracted considerable attention due to their ability to produce abundant cytokines and versatile roles in host defense, tissue regeneration, inflammation, and autoimmune diseases. Both αβT and γδT cells develop in the thymus. Unlike the development of αβT cells, which depends on αβTCR-mediated positive and negative selection, the development of γδT cells, including the requirement of γδTCR, has been less well understood. αβT cells differentiate into effector cells in the peripheral tissues, whereas γδT cells acquire effector functions during their development in the thymus. In this review, we will discuss the current state of knowledge of the molecular mechanism of TCR signal transduction and its role in the thymic development of γδT cells, particularly highlighting a newly discovered mechanism that controls proinflammatory γδT cell development.